Adrenal crisis in metastatic breast cancer - Doleschal, Bernhard (BMJ Case Rep, 2017)
A female patient with oestrogen receptor-positive and human epidermal growth factor receptor 2 (HER2)-positive invasive lobular breast cancer presented with progressive disease on CT scan. Some days after initiation of antineoplastic chemotherapy and anti-HER2 targeted antibody therapy, the patient presented with profuse diarrhoea, neutropaenia, nausea and weakness. Although Clostridium difficile was rapidly tackled as a causative agent of gastrointestinal complaints, clinical situation did not markedly improve despite proper antimicrobial treatment. The patient reported profound lack of energy, while nausea, vomiting and loose stools still persisted. Additionally slightly exaggerated pigmentation of nonsunexposed skin and mucosal areas led us to the assumption of proopiomelanocortin-derived peptide hypersecretion. The combination of highly elevated adrenocorticotropic hormone and low basal cortisol levels taken from a morning blood sample established the diagnosis of adrenal insufficiency due to metastatic burden, leading to a near Addison crisis by gastrointestinal complications of chemo-immune therapy. Administration of hydrocortisone immediately relieved general symptoms.